An Examination of Motivation to Change and Neural Alcohol Cue Reactivity Following a Brief Intervention - Grodin, Erica N.; Lim, Aaron C.; MacKillop, James; Karno, Mitchell P.; Ray, Lara A. (Frontiers in Psychiatry, 2019)
Background: Brief interventions represent a promising psychological intervention targeting individuals with heavy alcohol use. Motivation to change represents an individual’s openness to engage in a behavior change strategy and is thought to be a crucial component of brief interventions. Neuroimaging techniques provide a translational tool to investigate the neurobiological mechanisms underlying potential mediators of treatment response, including motivation to change. Therefore, this study aimed to examine the effect of a brief intervention on motivation to change drinking behavior and neural alcohol taste cue reactivity. Methods: Non-treatment-seeking heavy drinkers were randomized to receive a brief drinking intervention (n = 22) or an attention-matched control (n = 24). Three indices of motivation to change were assessed at baseline and after the intervention or control session: importance, confidence, and readiness. Immediately following the intervention or control session, participants also underwent an fMRI during which they completed an alcohol taste cues paradigm. Results: There was a significant effect of the brief intervention on increasing ratings of importance of changing drinking behavior, but not on ratings of confidence or readiness to change. Ratings of importance after the intervention or control session were associated with neural alcohol taste cue reactivity, but notably this effect was only significant for participants who received the intervention. Individuals in the intervention condition showed a positive association between ratings of importance and activation in the precuneus, posterior cingulate, and insula. Conclusions: The brief drinking intervention was successful at improving one dimension of motivation to change among non-treatment-seeking heavy drinkers. The brief intervention moderated the relationship between ratings of importance and brain activation in circuitry associated with interoceptive awareness and self-reflection. Together findings represent an initial step towards understanding the neurobiological mechanisms through which a brief intervention may improve motivation to change.